Subacute Sclerosing Panencephalitis: A Clinical, Radiological, and Outcome Study of 144 Cases - Jerry A George; Venugopalan Y Vishnu; Roopa Rajan; Mamta B Singh; Rohit Bhatia; Shariq Shah; Ajay Garg; Pradeep Venkatesh; Achal K Srivastava; Manjari Tripathi; MV Padma Srivastava; Anu Gupta (Annals of Indian Academy of Neurology)
Background and Objectives: Subacute sclerosing panencephalitis (SSPE) is a progressive encephalitis caused by persistent measles virus infection and is mostly described as small case series in literature. We aimed to describe the clinical spectrum, radiological features, outcomes, and prognostic factors in patients with SSPE and provide a comparison of childhood- versus late-onset disease. Methods: An observational study was conducted in a tertiary hospital in India, documenting the spectrum and functional outcome [modified Rankin Scale (mRS)] of patients with SSPE. Results: We enrolled 144 patients (35 prospective and 109 retrospective, mean age: 16.7 ± 5.0 years, 79.9% males) of SSPE (Dyken’s criteria), who presented between 2015 and 2022. Overall, we found good outcome (mRS ≤3) in 23.3% of cases and mortality in 48% (follow-up: n = 73/144, range 6–95 months). Short-term follow-up (prospective group, 32/35) revealed stabilization (no improvement or worsening of mRS) in 31.3% of patients, improvement of mRS grade in 28.1% patients, and worsening in 40.6% of patients. Intrathecal interferon was prescribed in majority of these cases, and 65.6% (21/32) were compliant to therapy. Frequency of good outcome reduced with longer follow-up duration (34.4% when followed up to 11 months, 22.2% for a follow-up duration of 24–60 months, and 10% for duration longer than 60 months). The studied outcome predictors were not statistically significant. Late-onset cases were different from childhood-onset cases with respect to some clinical features [more focal deficits (P = 0.043), less-frequent seizures (P = 0.003)], radiological features [more frequent cortical lesions (P = 0.44) and cerebral atrophy (P = 0.52)], and mortality [late-onset cases: 55.2% vs. childhood-onset cases: 33.3% (P = 0.08)]. Conclusion: We found differences in the presentation of childhood- versus late-onset disease. Overall, the prognosis was not good, with increasing mortality observed with increasing duration of follow-up. Short-term outcomes were better. Future studies can look at the effect of immunomodulators on long-term outcomes in a larger sample size.